Synthesis and characterization of chiral compounds containing cationic groups as chiral dopants in liquid crystals - Xie, Kongliang; Zhang, Chunxiang; Yu, Yanhong (Journal of colloid and interface science, 2011)
Novel chiral molecules containing cationic groups were synthesized. They had good optical activity and could convert nematic liquid crystals to cholesteric liquid crystals. [Display omitted] ► We designed and synthesized two novel chiral molecules containing cationic groups as functional surfactants for host liquid crystals (LCs). ► The novel chiral molecules containing cationic groups had good optical activity. ► Cationic polar groups did not affect optical rotation direction, but could influence the molar rotation of chiral compounds. ► These chiral molecules could convert nematic phase liquid crystals to cholesteric phase liquid crystals. Novel chiral molecules containing cationic groups, (N-[4-triethylammoniomethyl]-benzoyl ester)-ethyl lactate chloride and bi-(N-[4-triethylammoniomethyl]-benzoyl ester)-isosorbide chloride, were designed and synthesized. Chemical structures of the molecules were characterized by elemental analysis, FT-IR, and 1H NMR. The photochemical properties of the chiral compounds and their textures in nematic liquid crystals (LCs) were investigated by optical rotation, circular dichroism (CD), and polarizing optical microscopy (POM). The novel chiral molecules exhibited good optical activity. The chiral compound based on a l-ethyl lactate chiral center had a left-handed configuration. The chiral compound based on an isosorbide chiral center had a right-handed configuration. The cationic polar groups did not affect the direction of optical rotation, but could effluence the molar rotation of chiral compounds. The mixtures with dopants showed oily streak textures. Doping of a nematic phase liquid crystal with the chiral molecules converted it to the cholesteric phase.